Sociabilidade homoerótica masculina no Rio de Janeiro na década de 1960: relatos do jornal O Snob - Costa, Rogério da Silva Martins da (2010)
This work is a study about a network of homoerotic sociability in Rio de Janeiro in the 1960s. Its main object are reports and accounts found in a home-produced publication produced by one, and circulated among the groups participating in the network – O Snob. The network was composed of various social groups that had been forming since the 1950s, and most participants worked out their personal identities by sharing with the larger society the belief that homoerotic individuals belonged to the 'third sex', 'suffering' from what was considered sexual inversion. Thus a peculiar for mof sociability developed – centered around parties and festive gatherings at people’s houses as a survival strategy, since the expectations of sociosexual groups were surrounded by hostility in the larger society. This study indicates which processes of sociability were going on in the network, and how such sociability, moulded in invisibility, turned out to be – though in a non-articulated or involuntary way – a basic experience in social action and in the achievement of civil rights. It promoted practices that enabled its members to attend to meetings and that can be translated as a pursuit of the right to come and go, the right to freedom of expression, albeit in a segregated (or secret?) space. Those basic rights, however, were not guaranteed to the participants of the network. There is evidence that over the period studied homoerotic groups underwent a process of resignification and redefinition of identity.